Assessment on Drinking Water Handling and Sanitation Practices in an Urban Community of Imphal East, Manipur: A Cross-Sectional Study - Oinam, Joymati; Ningombam, Joenna Devi (National Journal of Community Medicine, 2021)
Background: According to SDG 6: Clean water and sanitation, each day, nearly 1000 children die due to preventable water and sanitation-related diarrheal diseases. The objectives of the study were to assess drinking water handling and sanitation practices in an urban community and its association with selected variables of interest. Methods: A cross-sectional study was conducted among 150 married women with under-five children from May to June 2018. From a randomly selected village in an urban community, participants were selected by convenience sampling. A predesigned, semi-structured questionnaire was used. Statistical tests like mean, SD, Chi-squared test, Fischer Exact test were used taking p-value <0.05 as statistically significant. Results: Only 18.9% of the respondents had improved main source of drinking water. Almost all (98%) had improved sanitation facilities of household. Statistically significant association were found between mothers with more than 30 years age group with adequate status of water treatment, sanitary status of under-five stool disposal and higher educational status of mothers with improved status of water treatment, sanitary status of under-five stool disposal. Conclusion: Only one-fifth of the respondents had improved main source of drinking water. Awareness campaigns should be conducted focusing on adequate water treatment and sanitary method of under-five stool disposal practices.